Research progress of near-infrared fl uorescence immunoassay - Xiao Hui Chang; Jie Zhang; Lin Huan Wu; Yan Kun Peng; Xiang Ying Yang; Xiao Lin Li; Ai Jin Ma; Jun Cai Ma; Guang Quan Chen (International Journal of Nanomaterials, Nanotechnology and Nanomedicine - Peertechz Publications, 2019)
Near-infrared fl uorescence immunoassay has been widely studied in the bio analytical fi eld. This review mainly introduces the basic principles of near-infrared spectroscopy and near-infrared detection technology, and summarizes the properties, characteristics and recent improvement of optical properties and signal intensity of three near-infrared fl uorescence probes (i.e. organic fl uorophores, quantum dots and rare earth compounds). We describe the applications of near-infrared fl uorescence technology in immunoassay, and prospect the application potential of lateral fl ow assay (LFA) based on this probe in the rapid detection of pathogens. Our team intends to establish a new platform which has highly sensitive near-infrared fl uorescence probes (NIFPs) combined with portable and simple immunochromatographic test strips (ICTSs) for rapid detection of food borne viruses. This will provide technical support for a rapid detection on the port. Practical applications The applications of near-infrared fl uorescence probes (NIFPs) in immunological analysis and clinically important biomarkers were also elaborated. Moreover, NIFPs-based immunoassay adaptable for rapid detection of foodborne pathogens was also forecasted. In 2017, our team has developed an approach for detecting pathogens such as Salmonella, Vibrio parahaemolyticus, Vibrio cholerae and Listeria monocytogenes by near-infrared immunoassay.